Students’ Critical Thinking Ability on Solving 6th Grade Mathematical Problems at SD Hang Tuah 10 Juanda - Pingki Maulidta Sari; Ida Sulistyawati; Via Yustitia (Urogram Studi Pendidikan Matematika, Universitas IVET, 2021)
Students' critical thinking ability in solving FPB and KPK material stories in grade IV is relatively low. The lack of critical thinking ability of these students is because students are not familiar with the question that refers to the level of critical thinking. So that students' critical thinking skills become uneceptible. The purpose of this study is to find out the critical thinking ability of students in working on FPB and KPK stories. This research uses descriptive qualitative research. The subject of this study was IVC grade students at SD Hang Tuah 10 Juanda as many as 6 students. The technique used is purposive sampling by using data collection method in the form of tests as many as 4 description questions. The results of this study showed that students have not been able to identify information from problems based on story problems, students have not been able to formulate or determine the subject matter, some students are able to solve problems with a variety of alternative solutions correctly, there are also some students who are able to solve problems but with incorrect calculations, and most students have not been able to draw clear conclusions for all problems , and only a small percentage of students are able to draw conclusions correctly. Students find it difficult to work on the problem because they do not understand the concept. Keywords: critical thinking, a matter of story, FPB and KPK